2013
DOI: 10.1093/infdis/jit827
|View full text |Cite
|
Sign up to set email alerts
|

IFNL4-ΔG Genotype Is Associated With Slower Viral Clearance in Hepatitis C, Genotype-1 Patients Treated With Sofosbuvir and Ribavirin

Abstract: Response to pegylated interferon-alpha and ribavirin (IFN-α/RBV) treatment for chronic hepatitis C virus (HCV) infection is influenced by host genetic factors, but their role for IFN-α-free, direct-acting antiviral (DAA) regimens is unclear. An exonic deletion allele (IFNL4-ΔG) bolsters the established association with IFN-α/RBV therapy treatment outcome of another IFNL4 variant, rs12979860, which is located upstream of IFNL3 (IL28B). We report that in patients treated with the DAA sofosbuvir along with RBV, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 15 publications
9
69
0
Order By: Relevance
“…However, there are several clinical as well as scientific reasons to pursue a deeper understanding of how IFNL genotype impact viral clearance. Several recent studies show that rs368234815 influences the response kinetics to DAA 28,30 ; however, the role of rs117648444 in DAA treatment has not yet been investigated. This suggests that patients not expressing IFNl4 can receive a shortened DAA treatment and possibly also reduced doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several clinical as well as scientific reasons to pursue a deeper understanding of how IFNL genotype impact viral clearance. Several recent studies show that rs368234815 influences the response kinetics to DAA 28,30 ; however, the role of rs117648444 in DAA treatment has not yet been investigated. This suggests that patients not expressing IFNl4 can receive a shortened DAA treatment and possibly also reduced doses.…”
Section: Discussionmentioning
confidence: 99%
“…Relative expression of IFNs or their receptors in EOT liver biopsies did not differ by treatment outcome (Figure 8, A-D), although this analysis was limited by the absence of pretreatment liver biopsies, precluding assessment of longitudinal changes. We genotyped all samples (n = 33) for 3 genetic variants associated with HCV clearance: the intronic rs12979860-C/T (29,30) and exonic rs368234815-TT/ΔG (31,32) of IFNL4 and the 3′ untranslated region (UTR) rs4803217-T/G of IFNL3 (Supplemental Tables 1 and 5 and ref. 33).…”
Section: Resultsmentioning
confidence: 99%
“…Genotyping of IFNL4 variants rs12979860-T/C and rs368234815-TT/ΔG (originally designated as ss469415590) was performed using genomic DNA samples and custom-designed TaqMan assays as previously described (31,32). rs4803217-T/G was genotyped with a custom-designed TaqMan assay: forward primer, CTGTGTGTCT-GACCCTTCCG; reverse primer, TCCTGGAGGTGAGTTGGATT-TAC; probe for allele T, CAATAAATTAAGACAAGTGGCTA (VIC, MGB); probe for allele G, ATAAATTAAGCCAAGTGGCTA (FAM, MGB).…”
Section: Genotypingmentioning
confidence: 99%
“…Recent studies have reported the dependence of viral kinetics on SNPs even in IFN-free treatment regimens 59,60 and recent trials with some two-DAA combinations without PR have been stunningly successful with 490% SVR in previous null responders to PR 61 . We speculate that this success may arise from a combination of three modes of DAA action.…”
Section: Discussionmentioning
confidence: 99%